1989
DOI: 10.21273/hortsci.24.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Control of Superficial Scald of Apples: A Review

Abstract: Superficial scald (storage, common scald) is an extensively studied postharvest physiological disorder of apples. Research on superficial scald of apples before 1965 was reviewed by Hardenburg (26); that reported since is summarized in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Superficial scald is a common physiological disorder of apples during the late stage of low-temperature storage (Ingle et al 1989). Studies have shown that cytosine methylation-based epigenetic regulation is involved in scald resistance (Karagiannis et al 2018), and a crucial role of polyphenol oxidase (PPO) and especially of the glutathione S-transferase (GST) protein in scald progress has been suggested (Karagiannis et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superficial scald is a common physiological disorder of apples during the late stage of low-temperature storage (Ingle et al 1989). Studies have shown that cytosine methylation-based epigenetic regulation is involved in scald resistance (Karagiannis et al 2018), and a crucial role of polyphenol oxidase (PPO) and especially of the glutathione S-transferase (GST) protein in scald progress has been suggested (Karagiannis et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Superficial scald is a common physiological disorder of apples during the late stage of low‐temperature storage (Ingle et al . 1989). Studies have shown that cytosine methylation‐based epigenetic regulation is involved in scald resistance (Karagiannis et al .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of storage conditions on the abundance of (E,E)-α-farnesene is important, as although (E,E)-α-farnesene with its green, oily and fatty notes contributes mainly to the vegetable descriptor of apple fruit [85], the products of (E,E)-α-farnesene oxidation could induce scald disorder [86][87][88]. The superficial scald of fruit is induced with prolonged storage at low temperature, and its severity is related to the storage temperature [89].…”
Section: Discussionmentioning
confidence: 99%